RELATIONSHIP BETWEEN FAMILY SUPPORT WITH ANXIETY LEVEL IN APPENDICTOMY PREOPERATIVE PATIENTS AT PROF .Dr.SOEKANDAR HOSPITALS MOJOSARI MOJOKERTO DISTRIC - W, Binarti Dwi (S1 Keperawatan, 2015)
Family support are attitude, action and acceptance family towards patients who get illness. The. The anxiousness is part of humanâs life that signed by fearfullness or deeply nervousness and having a continously. This research purposes to determine the relationship of family support with anxiety levels in appendictomy preoperative patients at Prof. Dr. Soekandar hospitals Mojokerto. This research is a correlational research with cross sectional approach. The population was all apendictomy preoperative patients. The sampling method was consecutive sampling. The analysis of the relationship of family support and the level of anxiety apply Spearman Rho correlation test showed a significant relationship with p = 0.004 (